Nursing care of a patient in terminally ill cancer - case study - Anna Surowiecka; Wojciech Garczynski; Anna Szczepanska; Walery Zukow (Journal of Education, Health and Sport, 2011)
The aim was to show the nurses and hospice care as a member of the team over the patient in a hospice for terminally ill cancer resident in the house. Nurse choosing to work with patients who die must know that not only medical knowledge will be needed in carrying out its duties but also a lot of love, patience and above all humility toward life and death. Characterized range of palliative care and its residents. The paper presents a description and policies for hospices and home desktops and volunteers working in them. Material - the subject of research - the case of a patient with pancreatic cancer he cultivated to the last moments of life. Test method - method of individual cases, which applies to nursing, is a qualitative description of the passage of reality and its interpretation. Used to collect all kinds of information about the case, in particular about the family situation, social, environmental, material and existential, psychological, physical or other person examined. This is a descriptive study undertaken by type of research problem, which requires the use of methods relating to a single case or small their number. Research problems: 1. How long the patient has symptoms associated with cancer diagnosed? 2. Have there been cases of death from cancer in the family sick? 3. Have you previously was treated oncological? 4. When the first signs of disease? 5. Does the patient know about his condition? 6. Are they symptomatic treatment introduced hospice doctor brings relief from symptoms? 7. Is recommended to take the product (Megace) improves the appetite, gives the desired effect? 8. Is your oxygen therapy brought relief in breathing? 9. How effective were notmorphotic painkillers? 10.Do you sick of the constant care exercised a family? 11. Is the hospice team visits took place at regular intervals or whenever the call of the family? 12. Is the patient dying in dignity, surrounded by kin? The goal of the research work presented, a description of the patient (the subject of research), research problems and the method of research, technology and research tools, describes the results of research. Presented in a special way and meaningful roles of a nurse who has the care of the patient in the terminal stage of cancer, staying at home. The problem of mental, spiritual, and emotional problems of the patient and the environment. Based on the literature of the subject and based on scientific study, the following conclusions: 1. In view of the cancer patient who is not eligible for treatment at the forefront the problem of cancer pain and other ailments of the digestive and respiratory systems, and greatly reduced physical fitness. 2. The patient was the biggest problem was lack of appetite and emaciation of the body related to it which greatly limited its self-care, and in a later stage, prevented completely. 3. Above the patient in the terminal who will remain in the home should be planned nursing care consulting and communicating with members of her family, educating them in implementing the active care, care and assist. 4. The nurse takes action on dying nursing care aimed at improving the quality of life, eliminating pain, psychological comfort, elimination of other ailments associated with the disease, assist.